Keberkesanan kaedah pengurusan fasiliti dan penyumber luaran terhadap prestasi bangunan - Ismail, Nordin Varseh; Osman, Wan Nadzri (Universiti Teknologi Malaysia, 2016)
Intense competition, higher wages, economic factors and the lack of internal labor, force organizations to look for alternatives to reduce costs and at the same time still maintaining existing performance. Similarly, the facility management of a building, especially involving government-owned buildings face the same phenomena.One popular method being used to overcome these phenomena is via outsourcing.Many organizations nowadays prefer to adopt outsourcing rather than internal contract practice.This resulted from the changes in the business environment that is focused towards effective operations.